Of Other Thoughts: Non-Traditional Ways to the Doctorate
XII, 336 p.
Keywords: Of Other Thoughts offers a path-breaking critique of the traditions underpinning doctoral research. Working against the grain of traditional research orthodoxies, graduate researchers (almost all from Indigenous, transnational, diasporic, coloured, queer and ethnic minorities) AND their supervisors offer insights into non-traditional and emergent modes of research—transcultural, post-colonial, trans-disciplinary and creative practice-led. Through case studies and contextualizing essays, Of Other Thoughts provides a unique guide to doctoral candidates and supervisors working with different modes of research. More radically, its questioning of traditional assumptions about the nature of the literature review, the genealogy of research practices, and the status and structuring of the thesis creates openings for alternative modes of researching. It gives our emerging researchers the courage to differ and challenges the University to take up its public role as critic and conscience of society. Barbara Bolt / Associate Professor and Associate Director of Research and Research Training / The Victorian College of the Arts /University of Melbourne / Australia These writings are essential reading for all PhD students interested in making their critical work count for more. They examine multiple sites where conservative politics and ethics, institutional regulations, culturally constrained supervisory practices, and disciplinary boundary maintenance run counter to the radical and transforming potential of critical PhD work. Graham Hingangaroa Smith / Distinguished Professor / Vice-Chancellor/Chief Executive Officer / Te Whare Wānanga o Awanuiārangi/ Whakatāne / Aotearoa – New Zealand This book makes a distinctive and valuable contribution to the growing literature on doctoral education. Readers will find a wonderfully diverse collection of perspectives on non-traditional paths to the PhD. The book synthesises theory with practice in a highly effective andengaging manner. It sets doctoral experiences in their broader cultural, political and intellectual contexts, and addresses epistemological and methodological questions with fresh insight. Of Other Thoughts will appeal to students and supervisors in a range of different fields and deserves a wide international readership. Peter Roberts / Professor of Education, University of Canterbury / Christchurch / Aotearoa – New Zealand.